Stancetaking and Language Ideologies in Heritage Language Learner Classroom Discourse. Issue 5 (3rd September 2017) - Showstack, Rachel E.
ABSTRACT: Drawing on linguistic anthropological notions of language ideologies and sociolinguistic approaches to stance, this study examines the meaning-making resources through which Spanish heritage language (HL) learners orient toward ideological perspectives on language value and linguistic expertise in classroom interaction. Part of a larger ethnographic study, data in the present study include about 26 hours of audio and video recordings from three different intermediate Spanish HL classrooms and filmed interviews with the students. The analysis indicates that discourses of legitimacy and expertise are embodied within multiple levels of classroom interaction, including affective stancetaking, expert/novice positioning, and the reframing of both ascribed social positions and previous discourse. Results suggest that the role of language ideologies in HL learning can be better understood through an examination of stancetaking in interaction and that the construction of different kinds of expertise should be an important consideration in the development of HL instructional practices.